The Dissection of SNAREs Reveals Key Factors for Vesicular Trafficking to the Endosome-like Compartment and Apicoplast via the Secretory System in Toxoplasma gondii - Shinuo Cao (American Society for Microbiology, 2021)
ABSTRACT Vesicular trafficking is a fundamental cellular process involved in material transport in eukaryotes, but the diversity of the intracellular compartments has prevented researchers from obtaining a clear understanding of the specific functions of vesicular trafficking factors, including SNAREs, tethers, and Rab GTPases, in Apicomplexa. In this study, we analyzed the localization of SNAREs and investigated their roles in vesicular trafficking in Toxoplasma gondii. Our results revealed the specific localizations of SNAREs in the endoplasmic reticulum (ER) (T. gondii Stx18 [TgStx18] and TgStx19), Golgi stacks (TgGS27), and endosome-like compartment (TgStx10 and TgStx12). The conditional ablation of ER- and Golgi-residing SNAREs caused severe defects in the secretory system. Most importantly, we found an R-SNARE (TgVAMP4-2) that is targeted to the apicoplast; to our knowledge, this work provides the first information showing a SNARE protein on endosymbiotic organelles and functioning in vesicular trafficking in eukaryotes. Conditional knockout of TgVAMP4-2 blocked the entrance of TgCPN60, TgACP, TgATrx2, and TgATrx1 into the apicoplast and interfered with the targeting of TgAPT1 and TgFtsH1 to the outermost membrane of the apicoplast. Together, our findings revealed the functions of SNAREs in the secretory system and the transport of nucleus-encoded proteins to an endosymbiotic organelle in a model organism of Apicomplexa. IMPORTANCE SNAREs are essential for the fusion of the transport vesicles and target membranes and, thus, provide perfect targets for obtaining a global view of the vesicle transport system. In this study, we report that a novel Qc-SNARE (TgStx19) instead of Use1 is located at the ER and acts as a partner of TgStx18 in T. gondii. TgGS27 and the tethering complex TRAPP III are conserved and critical for the biogenesis of the Golgi complex in T. gondii. A novel R-SNARE, TgVAMP4-2, is found on the outermost membrane of the apicoplast. The transport of NEAT proteins into the secondary endosymbiotic organelle depends on its function. To our knowledge, this work provides the first mention of a SNARE located on endosymbiotic organelles that functions in vesicular trafficking in eukaryotes.